KARAKTERISTIK PERUSAHAAN YANG MEMPENGARUHI TAX AVOIDANCE (Studi Empiris pada Perusahaan Manufaktur Non Logam yang terdaftar di Bursa Efek Indonesia Tahun 2016-2018) - Kurniawati, Lintang; Kholis, Nur (Prosiding University Research Colloquium, 2020)
The study aims to determine the effect of the independent variables namely company size, sales growth, leverage, capital intensity and independent commissioners on tax avoidance in non-metal manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The total sample of the study was 54 financial statements of non-metal manufacturing companies which were determined based on the purposive sampling method. The data collection method used is the documentation method in the form of financial statements of non-metal manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. Hypothesis testing using multiple regression analysis with the SPSS 21 program and previously tested classic assumption. The results of this study indicate that company size, sales growth and capital intensity effect tax avoidance. While leverage and independent commissioners have no effect on the tax avoidance